Detection of Chyle Leakage Site With Lymphoscintigraphy SPECT/CT in a Patient With Chylothorax Secondary to T-Cell Lymphoblastic Leukemia - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2022)
We present a pediatric case with T-cell lymphoblastic leukemia and persistent chylothorax who was referred to lymphoscintigraphy to identify the site of leakage. Planar lymphoscintigraphy with SPECT/CT revealed hot spots at the left jugulovenous angle and the confluens of the vena brachiocephalica to vena cava, which were compatible with the sites of leakage. Hybrid imaging with SPECT/CT technique have great impact on accurate detection of the defects in the lymphatic system in patients with chylothorax.
Keywords: chylothorax; Tc-99m-nanocolloid; lymphoscintigraphy; SPECT/CT; TOMOGRAPHY